2022
DOI: 10.21608/ejhm.2022.270288
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Outcomes of Hyperglycemia in Low Birth Weight Infants: A Prospective Observational Study

Abstract: Background: Low birth weight (LBW) babies frequently have hyperglycemia, which is linked to greater mortality as well as morbidity. The threshold intervention and management protocols are controversial. Objectives: To define the incidence of neonatal hyperglycemia, associated risk factors, and the outcome in LBW infants in tertiary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…In such cases, adequate fluid therapy and frequent glucose monitoring (every 1-2 h) are necessary (12). Recent studies have shown the effectiveness of continuous glucose monitoring (CGM) in regulating glucose levels and reducing the risk of both high and low blood sugar in preterm infants (5,14). In the case in the present study, CGM was commenced after a hyperglycaemic episode that reached 451 mg/dl and peaked at 465 mg/dl.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…In such cases, adequate fluid therapy and frequent glucose monitoring (every 1-2 h) are necessary (12). Recent studies have shown the effectiveness of continuous glucose monitoring (CGM) in regulating glucose levels and reducing the risk of both high and low blood sugar in preterm infants (5,14). In the case in the present study, CGM was commenced after a hyperglycaemic episode that reached 451 mg/dl and peaked at 465 mg/dl.…”
Section: Discussionmentioning
confidence: 70%
“…Case reports on neonatal hyperglycaemia are limited, particularly from Indonesia. The present study found six international case reports that are summarised in Table II (15)(16)(17)(18)(19)(20) and Table III (4)(5)(6)(7)(8). No definitive guidelines for neonatal hyperglycaemia have been established to date, at least to the best of our knowledge (10).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations